2011
DOI: 10.1080/15332691.2011.588095
|View full text |Cite
|
Sign up to set email alerts
|

Contributing Factors in the Therapeutic Alliance

Abstract: The therapeutic alliance is critical in couple therapy. Recent research has explored what factors might contribute to its creation. This study looks at two such factors: client stage of change and symptom distress, and how the relationship between symptom distress and the alliance might be mediated by client stage of change. The sample for this study was composed of 181 couples attending therapy for relationship problems. Participants completed questionnaires at intake and following the fourth session. Signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…In addition to gender differences in the quality of relationships with workers, some studies that examined working alliances in therapy settings have proposed the moderating role of gender or gender differences in the association between other parental characteristics and the working alliance. Porter and Ketring (2011) showed that male participants’ distress significantly decreased working alliance quality with their therapists, whereas this relationship was not significant among female participants. Another example is Knerr et al’s (2011) study, which found that among male participants, the development and maintenance of strong working alliances were more strongly influenced by their partners’ factors than by their own.…”
Section: Literature Reviewmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition to gender differences in the quality of relationships with workers, some studies that examined working alliances in therapy settings have proposed the moderating role of gender or gender differences in the association between other parental characteristics and the working alliance. Porter and Ketring (2011) showed that male participants’ distress significantly decreased working alliance quality with their therapists, whereas this relationship was not significant among female participants. Another example is Knerr et al’s (2011) study, which found that among male participants, the development and maintenance of strong working alliances were more strongly influenced by their partners’ factors than by their own.…”
Section: Literature Reviewmentioning
confidence: 91%
“…Demographic (e.g., age) and socioeconomic characteristics (e.g., education, income, and employment) are significant factors (Cho et al, 2017; Knerr et al, 2011; O’Brien et al, 2012). In addition, parents’ positive beliefs about their engagement and psychological characteristics (e.g., depression) can affect their relationships with workers in home visiting (Porter & Ketring, 2011; Stargel et al, 2020). Finally, parents’ relational factors are important, such as quality relationships with partners and living arrangement status (O’Brien et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Bordin (1979) defines the therapeutic working alliance as including three features: an agreement on goals, an assignment of task or series of tasks and the development of bonds. Since the construct of a therapeutic working alliance was suggested by Bordin, investigations have been consistently published demonstrating sound construct validity in both the therapy and the educational change enterprises and establishing its presence and efficacy in these contexts (Ackerman & Hilsenroth, 2003; Duff & Bedi, 2010; Falkenström, Grastrom, & Holmqvist, 2013; Porter & Ketring, 2011; Siefert & Hilsenroth, 2014; Wampold, 2001).…”
mentioning
confidence: 99%